Fragility of Comparative Advantage in Higher Dimensions: An Experimental Investigation - Nowbutsing, Baboo M (Journal of Economics and Behavioral Studies, 2011)
In this study, an experimental analysis of the fragility of the law of the comparative advantage in higher dimensions is performed. Noussair et al (1995) invoked a trading environment similar to the 2 x 2 Competitive Ricardian Model (CRM) and observed the law of comparative advantage. In this experiment, the same experimental setting is invoked however the number of goods and countries is increased. There were three countries and three goods, two countries were categorised as ‘intermediate’ comparative advantage while one as ‘extreme’ comparative advantage. However, the Jones (1961)’s criterion for optimal assignment was satisfied. The experimental findings reveal the following (1) both the autarky model and the competitive model are rejected as a representation of the data but the competitive model performs better than the autarky model (2) the CRM does not predict the production pattern (3) the CRM does not predict pattern of trade (4) output prices do not converge to the prediction of the theoretical model. Thus the results support the claim of Deardoff (2005).